Pre-service teachers’ construction of meaning: an interpretive qualitative study - Fajardo Mora, Nestor Ricardo (Colombian Applied Linguistics Journal, 2013)
This research-based article presents an interpretive qualitative study with pre-service teachers of Social Studies, who construct their own meanings from social-studies texts through their roots of knowledge, their shared assumptions, and the intertextuality which are collectively related to the core category: Habitus. Using these strategies, the pre-service teachers employ their own values, understandings and representations of the world to construct meaning. The author of this research collected and analyzed the data through the methodology of Grounded Theory. Pre-service teachers’ artifacts and class video recordings were used as major sources to collect data over the period of one semester.